157k views
2 votes
Please i have 15 minutes​

Please i have 15 minutes​-example-1

1 Answer

5 votes

Answer:


x = (-\log 7)/(\log 7 - \log 2)

Explanation:


2^x = 7^(x + 1)

Take the log of both sides.


\log 2^x = \log 7^(x + 1)

Use properties of log.


x \log 2 = (x + 1) \log 7


x \log 2 = x \log 7 + \log 7


x \log 2 - x \log 7 = \log 7


x(\log 2 - \log 7) = \log 7


x = (\log 7)/(\log 2 - \log 7)


x = (\log 7)/(-(\log 7 - \log 2))


x = (-\log 7)/(\log 7 - \log 2)

User MAK
by
5.9k points